Hubungan Kecerdasan Emosional Dengan Tingkat Stres Perawat Pada Masa Covid-19 Di RSU Kabupaten Tangerang - Ayu Pratiwi; Yunike Edmaningsih; Tita Yulia; Mohamad Riki Fauzi (Jurnal Kesehatan, 2022)
Background: Pandemic covid-19 cause nurses to experience stress due to unstable emotions so easily angry, worried about exposed to covid-19, many duties and responsibilities can increase the workload so it takes high emotional intelligence to lower stress levels. Research objective: to find out whether there is the relationship of emotional intelligence with a nurse’s stress level on during covid-19 at RSU Kabupaten Tangerang. Research metode: using research quantitative descriptive correlation to find out variable emotional intelligence with a nurse’s stress level. Sampling technique are using total sampling with sample number 107 respondents. research resultsthe data analysis technique used is chi square test on emotional intelligence with nurse’s stress level, the results are p-value 0,000 <0,05 with pearson correlation 0,459 wich mean is relationship rate moderate. Conclusions : That there is a relationship of emotional intelligence with a nurse’s stress level on during covid-19 at RSU Kabupaten Tangerang. suggestion: The Nurses can do stress management, improve knowledge of high emotional intelligence to lower stress levels.